Penilaian Akhlak Siswa oleh Guru Pendidikan Agama Islam: Analisis Objektivitas dan Subjektivitas - Eprianto; Ari Koswara; Duski, Duski (PAI RAFAH, 2025)
Moral education is a core component of the Islamic Religious Education (PAI) curriculum, functioning to shape students’ character in accordance with Islamic values. However, the assessment process of moral behavior often faces a dilemma between objectivity (evaluation based on standardized criteria) and subjectivity (evaluation influenced by teachers’ personal perceptions). This study aims to analyze the epistemology of moral assessment conducted by Islamic Religious Education (PAI) teachers, focusing on the balance between objectivity and subjectivity as well as its implications for character formation. Using a qualitative method with a field study approach, data were collected through in-depth interviews with four Islamic Religious Education (PAI) teachers, participant observation, and classroom documentation, then analyzed using the Miles and Huberman model. The findings indicate that objective assessment is based on curriculum indicators such as honesty and discipline in worship, while subjectivity arises from teachers’ personal perceptions and experiences of students. Approximately 80% of the field data reveal a dominance of subjective assessment, particularly toward students with disciplinary issues. This condition creates potential bias and reduces fairness in evaluation. Therefore, teacher training and the development of standardized assessment rubrics are needed to make the moral evaluation process more measurable, fair, and effective in shaping students’ character in the digital era.